Answer:
(a) When a = 4 and b = -5, a² + b² - a·b = 61
(b) When a = 4 and b = -5, a³·b + a·b² = -220
(c)
![When \ a = 4 \ and \ b = -5, \ (a - b)/(a + b) + a -b = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/byuyi92uqbkdzplgchsvigc373neohgd4t.png)
(d) When a = 4 and b = -5, (a + b)² - (a - b)² = 82
Explanation:
The question relates to evaluation of expressions, given the values of the variables, "a" and "b"
Where;
a = 4 and b = -5
(a) For a² + b² - a·b, we have;
a² + b² - a·b = 4² + (-5)² - 4 × (-5) = 16 + 25 + 20 = 41 + 20 = 61
(b) For a³·b + a·b² we have;
a³·b + a·b² = 4³·(-5) + 4·(-5)² = 64 × (-5) + 4 × 25 = -320 + 100 = -220
(c) For
, we have;
![(a - b)/(a + b) + a -b = (4 - (-5))/(4 + (-5)) + 4 - (-5) = (4 + 5)/(4 -5) + 4 + 5= (9)/(-1) + 4 + 5 = -9 + 4 + 5 = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/y5mo6z2u48gup5coas9drmu0p6vcsgs991.png)
![\therefore when \ a = 4 \ and \ b = -5, \ (a - b)/(a + b) + a -b = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/3iev2jh5l5bdwa9n3cv2vxeg6q53quuzwc.png)
(d) For (a + b)² - (a - b)² we have;
(a + b)² - (a - b)² = (4 + (-5))² - (4 - (-5))² = (4 - 5)² - (4 + 5)² = (-1)² - 9² = 1 + 81 = 82
When a = 4 and b = -5, (a + b)² - (a - b)² = 82